Security and efficacy of intravenous injection of lidocaine in major hepatic resection - R. A. Zatsarynnyi; O. E. Sydiuk; O. O. Pidopryhora (Клінічна хірургія, 2022)
Objective. To determine in dynamics the blood lidocaine concentration in the patients while performing major hepatic resection with its epidural and intravenous injection for intra– and postoperative anesthesia and to estimate the toxicity potential.